PENGARUH DAYA TARIK PRODUK, WORD OF MOUTH, NILAI PELANGGAN TERHADAP MINAT BELI KONSUMEN DI ERA PANDEMI COVID-19 PADA SUPERMARKET CITRA NIAGA (SURVEY PADA KONSUMEN SUPERMARKET CITRA NIAGA DI KOTA PONTIANAK) - Steven Steven (Jurnal Ekonomi Integra, 2021)
The attractiveness of products, word of mouth, and good customer value will of course attract consumer buying interest in the midst of the corona virus (covid-19) pandemic. Customers who are satisfied with the product purchased will of course be loyal to the company concerned. This study wants to prove the effect of each variable, namely product attractiveness, word of mouth, and customer value on consumer buying interest in the era of the COVID-19 pandemic at Citra Niaga Pontianak supermarket. Based on previous research and linked to the supporting theory put forward by experts using the SPSS program as a statistical data processing tool. This type of research is associative research. In this study, researchers used a nonprobability sampling technique because the researcher did not know the total number of members of the population under study. While the sampling technique used in this study was accidental sampling with a population of 100 people as the sample.